The Akodon boliviensis species group (Rodentia: Cricetidae: Sigmodontinae) in Argentina: species limits and distribution, with the description of a new entity - Jayat, Jorge Pablo (2010)
Akodon, with about 42 living species, is the most diverse genus of the subfamily Sigmodontinae. The Akodon boliviensis species group includes small-bodied, morphologically similar forms inhabiting Altiplano grasslands and grassland/forest ecotones of the eastern slope of the Andes, from central Peru to central Argentina. Northwestern Argentina contains the largest diversity of species of the group; the taxonomic treatment of these species has been based largely on unsupported and some weakly based opinions as underscored by recurrent changes. Based on morphologic and molecular data we assessed species limits among Argentinean populations of the Akodon boliviensis species group. We conclude that four species of the A. boliviensis species group inhabit northwestern Argentina. These are: A. boliviensis; A. caenosus (under which we synonymyze A. aliquantulus); A. spegazzinii (of which the nominal forms alterus, leucolimnaeus, and tucumanensis are junior synonyms); and A. sylvanus. Additionally, we described here a new species of the A. Boliviensis species group, Akodon polopi, which inhabits central Argentina. This is the only species of the A. boliviensis species group inhabiting the Sierras Grandes range (ca. 2000 m), mountain system of medium height isolated (ca., 600 km) from the main Andean chain by low elevation arid and semiarid environments. Additionally, our phylogenetic analysis suggests that the Akodon varius species group is polyphyletic.